Competition and Market Concentration in the Municipal Bond Market - Cestau, Dario (SSRN, 2019)
Lack of competition among the underwriters of municipal bonds increases the borrowing costs of local municipalities. I find that the proportion of municipal bonds sold in competitive sales in the state has an economically significant effect on several measures of competitiveness. Competitive sales increase the number of active underwriters in the state and substantially decrease the concentration in the market for underwriting services for municipal bonds. I also find that state restrictions on the negotiated sale of municipal bonds can materially decrease market concentration. Market concentration has increased considerably over time, but only negotiated deals have contributed to greater concentration.
Keywords: Market power; Concentration; Herfindahl Index; Book building; Auctions; Municipal bonds; 53 Ciencias Económicas; ODS 8 - Trabajo decente y crecimiento económico